2017
DOI: 10.1016/j.molimm.2017.06.093
|View full text |Cite
|
Sign up to set email alerts
|

The role of CR3 (CD11b/CD18) and CR4 (CD11c/CD18) in complement-mediated phagocytosis and podosome formation by human phagocytes

Abstract: CR3 and CR4 belong to the family of β 2 -integrins and play an important role in phagocytosis, cellular adherence and migration. CR3 and CR4 are generally expected to mediate similar functions due to their structural homology, overlapping ligand specificity and parallel expression on human phagocytes. Although the different signalling pathways of these receptors suggest distinct functions, possible differences are just being revealed.Previously we proved that CR3 plays a key role in the uptake of iC3b-opsonize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…autosomal recessive disorder resulting in defective leukocyte adherence to the endothelium, neutrophil aggregation and chemotaxis, phagocytosis and cytotoxicity mediated by neutrophils, NK cells and T cells (van de Vijver et al, 2013). Additionally, Mac-1 deficiency in mice (Morrison et al, 2008;Carter et al, 2009) and in humans (van de Vijver et al, 2013;Lukacsi et al, 2017) was shown to be related to increased susceptibility to infections. Therefore, the possible association between CD11b expression levels and susceptibility to infection in NTD b°-thalassaemia/HbE patients should be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…autosomal recessive disorder resulting in defective leukocyte adherence to the endothelium, neutrophil aggregation and chemotaxis, phagocytosis and cytotoxicity mediated by neutrophils, NK cells and T cells (van de Vijver et al, 2013). Additionally, Mac-1 deficiency in mice (Morrison et al, 2008;Carter et al, 2009) and in humans (van de Vijver et al, 2013;Lukacsi et al, 2017) was shown to be related to increased susceptibility to infections. Therefore, the possible association between CD11b expression levels and susceptibility to infection in NTD b°-thalassaemia/HbE patients should be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…4A). After filtering for high abundance proteins found in at least three independent experiments, eight proteins were identified as putative sCD93 receptor components (Table 1), including three phagocytic integrin subunits (α x , β 2 , and β 1 ), CD44, and multiple integrin-associated signaling molecules, indicating that the sCD93 receptor is likely an integrin [28][29][30].…”
Section: Identification Of the Scd93 Receptormentioning
confidence: 99%
“…4F). α x β 2 is also a receptor for complement, suggesting that sCD93 and complement may act in concert [30]. Although the addition of human serum to sCD93-opsonized cells enhanced efferocytosis, depletion of complement with cobra venom or heat inactivation did not abrogate this effect, indicating that other serum-borne opsonins were responsible for this increase in opsonization (Supporting Information Fig.…”
Section: Identification Of the Scd93 Receptormentioning
confidence: 99%
“…While many proteins were non-specifically cross-linked to the sCD93 beads, filtering of the dataset for high abundance proteins found in at least 3 of 4 independent experiments identified only 8 proteins as putative sCD93 receptor components (Table 1). These included three phagocytic integrin subunits (αx, β2 and β1), CD44 which regulates integrin-mediated phagocytosis, and several integrinassociated signaling molecules, indicating that the sCD93 receptor is likely an integrin (43)(44)(45)(46). To determine which of these proteins function as the sCD93 receptor, αx, β1, β2, and CD44 deficient THP-1 cell lines were generated using lentiviral-shRNAs ( Figure 4B).…”
Section: Identification Of the Scd93 Receptormentioning
confidence: 99%